2020
DOI: 10.1080/15384101.2020.1743909
|View full text |Cite
|
Sign up to set email alerts
|

Propofol inhibited apoptosis of hippocampal neurons in status epilepticus through miR-15a-5p/NR2B/ERK1/2 pathway

Abstract: Although a previous study reported that propofol had a therapeutic effect in status epilepticus (SE), the mechanisms underlying the effect of propofol in SE remain unclear. The aim of this study was to explore the regulatory mechanisms underlying propofol-induced inhibition of SE.A rat SE model was established using the lithium-pilocarpine injection method. A qRT-PCR and Western blot were utilized to detect the expression of relative molecules. Cell apoptosis was evaluated by a flow cytometry assay. The intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Specifically, the following findings from cell culture models showed that miR-15a-5p [53], MicroRNA-582-5p [54] and miR-34a [55] were involved in propofol-induced neuron and astrocyte death, respectively; miR-21 was involved in propofol-induced inhibition of proliferation and epithelial-mesenchymal transition in breast cancer cells [56]; miR-495 was involved in propofol-induced inhibition of proliferation and metastasis in JEG-3 choriocarcinoma cells [57]. In this study, propofol treatment decreased cell migration followed by miR-34a and E-cadherin upregulation in the PANC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the following findings from cell culture models showed that miR-15a-5p [53], MicroRNA-582-5p [54] and miR-34a [55] were involved in propofol-induced neuron and astrocyte death, respectively; miR-21 was involved in propofol-induced inhibition of proliferation and epithelial-mesenchymal transition in breast cancer cells [56]; miR-495 was involved in propofol-induced inhibition of proliferation and metastasis in JEG-3 choriocarcinoma cells [57]. In this study, propofol treatment decreased cell migration followed by miR-34a and E-cadherin upregulation in the PANC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-34c has also been found to play a negative role in seizure and cognitive function, possibly by regulating NMDARs and AMPARs associated with LTP (Huang et al, 2018). Both in hippocampal tissues of SE rats and low Mg-induced hippocampal neurons, propofol can inhibit apoptosis of hippocampal neurons by microRNA-15a-5p/GluN2B/ERK1/2 pathway, which provides theoretical support for propofol treatment of SE (Liu et al, 2020). MicroRNA-124 suppresses seizure and regulates CREB1 activity.…”
Section: Microrna and Nmdarmentioning
confidence: 87%
“…In addition, miR-15a upregulation induces the expression of autophagy-related proteins, indicating that miR-15a is involved in AKT3-mediated autophagy via AKT3 inhibition. Moreover, miR-15a-5P targets NR2B in epileptic patients, negatively regulating its expression and inhibiting neuronal apoptosis in the hippocampus ( 77 ). The specific mechanism of miR-15a’s action in AD is unclear and requires further study.…”
Section: Role Of Non-coding Rnas In Ad Neuroinflammationmentioning
confidence: 99%